ANTI-BACTERIAL ACTIVITY TEST OF ETHANOL EXTRACTS AND ETHLACETATE FRACTION FROM THE EXTRACT OF JATROPHA CURCAS L. LEAVES AGAINST STAPHYLOCOCCUS AUREUS - Wulandari, Sekar; Erikania, Susanti; Maritha, Vevi (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Staphylococcus aureus is a gram-positive bacteria that can cause infection. One of the plants that has antibacterial activity is jatropha leaves which contain flavonoids, saponins, tannins, alkaloids, steroids and polyphenols. Purpose: To determine the antibacterial activity of ethanol extract and ethyl acetate fraction with concentrations of 30%, 60% and 100% against Staphylococcus aureus bacteria. Method: The method for extracting jatropha leaves is maceration with 96% ethanol solvent and the fractionation method, namely liquid-liquid fractionation with ethyl acetate solvent. Antibacterial activity test was carried out in vitro with the disc diffusion method and compared the mean zone of inhibition of each treatment with a positive control (gentamicin 10 μg). Result: The results showed that the ethanol extract and ethyl acetate fraction of jatropha leaves had a strong resistance response, while the positive control gave a very strong inhibitory response to the growth of S. aureus bacteria. Based on the one way ANOVA test, ethanol extract and ethyl acetate fraction showed a significant difference from each treatment with a significant value (P=<0.05). Conclusion: The ethanol extract of Jatropha leaves can inhibit the growth of S. aureus bacteria at a concentration of 100% (18.28 ± 0.50 mm), 100% concentration of ethyl acetate fraction (15.10 ± 0.12 mm). The ethanol extract provided the best inhibition power, namely 18.28 ± 0.50 mm and a positive control 21.82 ± 0.092 mm.